Pengaruh Promosi Jabatan, Kompensasi dan Stres Kerja terhadap Kinerja Karyawan PT. Tema (Trijaya Excel Madura) melalui Kepuasan Kerja - Wahyu Maulana (Business Management Analysis Journal (BMAJ), 2019)
Technological developments make economic actors to think continuously in order to survive. Individual must work hard to be the best. This condition tends to make employees depressed. The companies must act in order to produce the maximum performance and employee satisfaction in working. Based on the situation, the writer conducted a study to analyze the direct and indirect effect of the three independent variables (X) (job promotion, compensation, and job stress) on the dependent variable (Y) (work performance) through variable intervening (Z) (job satisfaction). Total samples in this study were 200 persons as the informants analyzed using PLS analysis. The results show that all independent variables have a significance effect on the job satisfaction; on top of that, it is an intervening variable for all the independent variables in this study. For the work stress variable, this does not have a significance effect on the employee performance; meanwhile, for the job promotion and compensation variables, those have a significance effect on the employee performance. The dominant variable of this study is the job promotion variable.